THE ABSOLUTE CHRONOLOGY OF COLLECTIVE BURIALS FROM THE 2ND MILLENNIUM BC IN EAST CENTRAL EUROPE. Issue 2 (28th April 2021) - Makarowicz, Przemysław; Goslar, Tomasz; Górski, Jacek; Taras, Halina; Szczepanek, Anita; Pospieszny, Łukasz; Jagodinska, Marina O; Ilchyshyn, Vasyl; Włodarczak, Piotr; Juras, Anna; Chyleński, Maciej; Muzolf, Przemysław; et al.
ABSTRACT: This article discusses the absolute chronology of collective burials of the Trzciniec Cultural Circle communities of the Middle Bronze Age in East Central Europe. Based on Bayesian modeling of 91 accelerator mass spectrometry radiocarbon (AMS 14 C) dates from 18 cemeteries, the practice of collective burying of individuals was linked to a period of 400–640 (95.4%) years, between 1830–1690 (95.4%) and 1320–1160 (95.4%) BC. Collective burials in mounds with both cremation and inhumation rites were found earliest in the upland zone regardless of grave structure type (mounded or flat). Bayesian modeling of 14 C determinations suggests that this practice was being transmitted generally from the southeast to the northwest direction. Bayesian modeling of the dates from the largest cemetery in Żerniki Górne, Lesser Poland Upland, confirmed the duration of use of the necropolis as ca. 140–310 (95.4%) years. Further results show the partial contemporaneity of burials and allow formulation of a spatial and temporal development model of the necropolis. Based on the investigation, some graves were used over just a couple of years and others over nearly 200, with up to 30 individuals found in a single grave.